2018
DOI: 10.21037/jtd.2018.04.12
|View full text |Cite
|
Sign up to set email alerts
|

Novel method of noninvasive ventilation supported therapeutic lavage in pulmonary alveolar proteinosis proves to relieve dyspnea, normalize pulmonary function test results and recover exercise capacity: a short communication

Abstract: Whole lung lavage (WLL) under general anesthesia with a double-lumen endobronchial intubation has remained standard treatment option for pulmonary alveolar proteinosis (PAP) for over fifty years now. To the best of our knowledge, this is the first description of noninvasive ventilation (NIV) as an innovative alternative, which enables safe and effective treatment. NIV support enabled cost-effective lavage of the most affected segments and resulted in restoration and long-term maintenance of exercise capacity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Therefore, it is recommended to collect specimen directly from the lower respiratory tract if possible. In particular in severe, intubated patients, the targeted BAL of the most involved lobe should be considered alongside the potential risk of using bronchofiberoscopy in such difficult setting [6]. The patient did not expectorate and standard BAL was not feasible due to the severity of patient' s condition.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is recommended to collect specimen directly from the lower respiratory tract if possible. In particular in severe, intubated patients, the targeted BAL of the most involved lobe should be considered alongside the potential risk of using bronchofiberoscopy in such difficult setting [6]. The patient did not expectorate and standard BAL was not feasible due to the severity of patient' s condition.…”
Section: Discussionmentioning
confidence: 99%
“…3 Recently, it was shown that lung lavage with flexible bronchoscopy (FB) is facilitated by NIV. 4 A potential alternative of NIV to treat respiratory failure is the nasal delivery of high-flow oxygen which refers to the entry of air and oxygen through a humidifier in a high-flow circuit. It has been shown that a flow of air of 40 L/min is well tolerated in adults and that the gas flowing during inspiration is maintained at the appropriate temperature and humidity.…”
Section: Introductionmentioning
confidence: 99%